Why machines will never rule the world Artificial Intelligence without fear - Landgrebe, Jobst; Smith, Barry 1952- (Routledge, an imprint of Taylor & Francis Group, 2025)
This book's core argument is that an artificial intelligence that could equal or exceed human intelligence is for mathematical reasons impossible. In supporting their claim, the authors marshal evidence from mathematics, physics, computer science, philosophy, linguistics, biology, and anthropology.
Keywords: Artificial intelligence-Philosophy; Artificial intelligence-Social aspects; Singularities (Artificial intelligence)-Forecasting